Crossing the line: Tunas actively exploit submesoscale fronts to enhance foraging success. Issue 5 (28th September 2017) - Snyder, Stephanie; Franks, Peter J. S.; Talley, Lynne D.; Xu, Yi; Kohin, Suzanne
Abstract: Fronts—i.e., the boundaries between water masses—are ubiquitous in the world oceans and have been shown to significantly influence pelagic ecosystems with enhanced local productivity and increased abundances of forage fish and top predators. Here we use data from archival tags to document how four juvenile albacore tunas foraged at and exploited a thermal front. Of the 3098 observed trips, the albacore mainly swam across the front between the warm side above the thermocline and the cold side below the thermocline with an average of 78 ± 20.4 cross‐frontal trips per fish per day. The warm frontal surface waters provided a thermal resource, allowing the tuna to maintain higher body temperatures and thus forage more efficiently in the food‐rich waters of the cold side of the front. Foraging success of the tunas decreased as the cross‐front thermal gradient weakened. This first look into small‐scale use of fronts by a top predator demonstrates that ephemeral, submesoscale oceanic features can play a significant role in pelagic ecology.